THE NECESSITY OF TOEFL CLASS FOR UNDERGRADUATE STUDENTS OF CIVIL AVIATION - Sukahir; Parjan; Umi Dian Adhitya Wulan Ningrum (Universitas PGRI Palembang, 2024)
This article is part of a report on the implementation of training activities to increase TOEFL scores for undergraduate students at the Palembang Polytechnic of Civil Aviation. The activities were carried out partly because some of the cadets had never taken a TOEFL test before. This descriptive research was conducted on this activity. The instruments were a needs analysis questionnaire for the students and an interview guideline for the lecturer. The method of implementing the activity is carrying out a TOEFL preparation class for a 4-hour lecture course. The results of the activity show that there is a significant increase in scores but taking into account that TOEFL is divided into three parts: listening, structure and written expressions, and reading comprehension, its preparation process for TOEFL is a long study course. Each unit has different abilities with 27 skills in the listening section, 60 in the structure and written expressions, and 14 in the reading section. Therefore, with a total of 101 skills to be mastered, a 4-hour lecture course is clearly insufficient.